Leukemia inhibitory factor inhibits erythropoietin-induced myelin gene expression in oligodendrocytes - Georgina Gyetvai; Cieron Roe; Lamia Heikal; Pietro Ghezzi; Manuela Mengozzi (BMC, 2018)
Abstract Background The pro-myelinating effects of leukemia inhibitory factor (LIF) and other cytokines of the gp130 family, including oncostatin M (OSM) and ciliary neurotrophic factor (CNTF), have long been known, but controversial results have also been reported. We recently overexpressed erythropoietin receptor (EPOR) in rat central glia-4 (CG4) oligodendrocyte progenitor cells (OPCs) to study the mechanisms mediating the pro-myelinating effects of erythropoietin (EPO). In this study, we investigated the effect of co-treatment with EPO and LIF. Methods Gene expression in undifferentiated and differentiating CG4 cells in response to EPO and LIF was analysed by DNA microarrays and by RT-qPCR. Experiments were performed in biological replicates of N ≥ 4. Functional annotation and biological term enrichment was performed using DAVID (Database for Annotation, Visualization and Integrated Discovery). The gene-gene interaction network was visualised using STRING (Search Tool for the Retrieval of Interacting Genes). Results In CG4 cells treated with 10 ng/ml of EPO and 10 ng/ml of LIF, EPO-induced myelin oligodendrocyte glycoprotein (MOG) expression, measured at day 3 of differentiation, was inhibited ≥4-fold (N = 5, P < 0.001). Inhibition of EPO-induced MOG was also observed with OSM and CNTF. Analysis of the gene expression profile of CG4 differentiating cells treated for 20 h with EPO and LIF revealed LIF inhibition of EPO-induced genes involved in lipid transport and metabolism, previously identified as positive regulators of myelination in this system. In addition, among the genes induced by LIF, and not by differentiation or by EPO, the role of suppressor of cytokine signaling 3 (SOCS3) and toll like receptor 2 (TLR2) as negative regulators of myelination was further explored. LIF-induced SOCS3 was associated with MOG inhibition; Pam3, an agonist of TLR2, inhibited EPO-induced MOG expression, suggesting that TLR2 is functional and its activation decreases myelination. Conclusions Cytokines of the gp130 family may have negative effects on myelination, depending on the cytokine environment.